HUBUNGAN ANTARA PENGETAHUAN STANDAR PROSES MOTIVASI KERJA DAN INOVASI GURU DENGAN KOMPETENSI PEDAGOGIK - Erni Erni (Jurnal Ilmu Pendidikan, 2012)
The purposes of this study were to determine the relationship between I) standard process knowledge with pedagogic competence, 2) work motivation with pedagogic competence, 3) teacher's innovation in learning with pedagogic knowledge 4) standard process knowledge, work motivation and teacher's inovation in learning with teacher's pedagogic competence in elementary school in the district of eastern Tanjung Karang Bandar Lampung study year 2011/2012. Research methods used correlational research. The population is all elementary school teachers in the District of Eastern Tanjung Karang Bandar Lampung. Sample as many as 54 people were assigned proportional random sampling. Instrument used to collect data is data analysis technique simple correlation.The results of the analysis of the study are : (1) there is a close, positive and significant relationship between the standard process knowledge with pedagogical competence of 0.576, (2) there is a relationship between motivation to work with pedagogical competencies of 0.607, (3) there is a relationship between innovation competence of teachers in the learning with pedagogic competence of 0.447, (4) there is a relationship between standard process knowledge, work motivation and innovation of teachers in learning together with the pedagogic competence of 0.741.Keywords: pedagogical competence, standard process knowledge, teacher's innovation, work motivation